Alternativas forrageiras para sistemas de recria de novilhas de corte - Roso, Dalton (2011)
Two experiments were carried out aiming to evaluate pasture attributes and productive and reproductive performance of beef heifers from nine to 13 months of age (Experiment 1) and subsequently from 15 to 18 months of age (Experiment 2). Pasture and livestock assessment in Experiment 1 totaled 112 days, from July to November 2008. The beef heifers were kept grazing on Italian ryegrass (Lolium multiflorum Lam), with heifers either exclusively on pasture or receiving fat as a supplement (0.15 or 0.30% of body weight (BW)). Experiment 2 was carried out from January to April 2009 and pasture attributes, productive and reproductive performance and beef heifers ingestive behavior in Coastcross (Cynodon dactylon (L.) with forage on offer (FO) of 10% and Alexandergrass (Urochloa plantaginea) with FO of 8 and 12% were studied. On both experiments continuous grazing method was used with variable number of animals. The experimental design was completely randomized with repeated measures over time. The following variables were measured in Experiment 1: animal performance, pasture and supplement efficiency of conversion to kg of body weight, height , body weight:height ratio, pelvic area and reproductive tract score of heifers. Pasture variables were similar between supplement levels and the average values of forage mass and forage on offer were 1497.6 kg ha-1 DM and 11.45 kg DM 100 kg-1 BW, respectively. The productive and reproductive variables were not affected by fat levels tested. Heifers supplemented with fat had higher average daily gain, body weight, height, condition score and body weight: height ratio than heifers exclusively on pasture. The use of supplemental fat promoted no change in pelvic area and reproductive tract score of heifers, which presents inadequate development to allow breeding at 12/14 months old. In Experiment 2, the ingestive behavior was measured in four continuous 12 hour periods. Pasture variables, animal performance and ingestive behavior in Alexandergrass were similar in both forage on offer. There was both stocking rate and gain per hectare increase of 22 and 75%, respectively when heifers grazed on Alexandergrass in relation to Coastcross. The heifers present similar individual and reproductive performance when grazing on either Coastcross or Alexandergrass on both forage on offer and are considered capable of breeding at 18 months of age.